Development of an RME-Based Digital Module with a Sundanese Cultural Context on Students' Numeracy Literacy Ability - Imswatama, Aritsya; Saepuloh, Luthpi (Universitas Suryakancana, 2025)
The purpose of this study was to develop a digital module based on RME with a Sundanese cultural context on students' numeracy literacy skills. This study used a type of research and development with the ADDIE model consisting of five stages, namely Analysis, Design, Development, Implementation and Evaluation. Data collection techniques in this study include interviews, observations and questionnaires. The results of this study state that this RME-based digital module is valid, practical and effective for use in mathematics learning. In this module there is an RME learning design combined with local wisdom of Sundanese culture so that abstract mathematics learning can be easily learned by students. In addition, there are numeracy literacy-based practice questions that can improve students' skills in working on literacy questions. This module is interactive digital so that in its implementation students can easily use gadgets or other computer devices. This module is designed using the RME approach, on the material of two-variable linear equation systems for class X. In this module, the RME learning principles are applied, namely dedactical phenomenology, Guided Reinvention and Self Developed Model, with the context of Sundanese cultural problems. The Sundanese cultural context used is related to typical Sundanese food, typical Sundanese equipment that is sold in the market and traditional Sundanese houses.